2018
DOI: 10.3389/fpsyt.2018.00100
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Comparing Behavioral, Educational, and Pharmacological Treatments in Youths With Chronic Tic Disorder or Tourette Syndrome

Abstract: ContextThe existing literature on the treatment of pediatric chronic tic disorder (CTD) and Tourette syndrome (TS) indicates that both behavioral therapy (BT) and pharmacotherapy (PT) are effective for reducing symptoms.ObjectiveTo evaluate the efficacy of BT compared to psychoeducation (PE) or PT for reducing tics and co-occurring symptoms and for improving quality of life (QoL) in a sample of youths with CTD and TS.DesignA 10 weeks, 2 sites (Catania, Rome) randomized controlled trial. Participants were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 32 publications
0
39
0
2
Order By: Relevance
“…In this study, we found evidence to support the e cacy of ERP for reducing obsession-compulsion and tic symptoms. Behavioral therapy and SRIs were found to be comparable in improving the symptoms in adults with OCD among three head-to-head RCTs [45], and ERP also exhibited comparable reductions in tic severity with habit reversal therapy (HRT) [46][47][48]. It appears that the mechanisms that underlie the treatment of OCD and tic disorders are similar to some extent.…”
Section: Meta-regression Analysismentioning
confidence: 89%
“…In this study, we found evidence to support the e cacy of ERP for reducing obsession-compulsion and tic symptoms. Behavioral therapy and SRIs were found to be comparable in improving the symptoms in adults with OCD among three head-to-head RCTs [45], and ERP also exhibited comparable reductions in tic severity with habit reversal therapy (HRT) [46][47][48]. It appears that the mechanisms that underlie the treatment of OCD and tic disorders are similar to some extent.…”
Section: Meta-regression Analysismentioning
confidence: 89%
“…Another randomized clinical trial concluded that behavioural therapy, including HRT, is as effective as pharmacological therapy in the treatment of tic disorders in children and adolescents (Rizzo, Pellico, Silvestri, Chiarotti, & Cardona, 2018). New guidelines released by the American Academy of Neurology recommend CBIT as the first-line treatment for patients with symptoms that interfere with daily activities (Pringsheim et al, 2019).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Recent randomized clinical trials have confirmed the effectiveness of CBIT in treating children and adults with TS and CTDs (Abramovitch et al, ; Deckersbach, Rauch, Buhlmann, & Wilhelm, ; Piacentini et al, ; Storch et al, ; Wilhelm et al, ). Another randomized clinical trial concluded that behavioural therapy, including HRT, is as effective as pharmacological therapy in the treatment of tic disorders in children and adolescents (Rizzo, Pellico, Silvestri, Chiarotti, & Cardona, ). New guidelines released by the American Academy of Neurology recommend CBIT as the first‐line treatment for patients with symptoms that interfere with daily activities (Pringsheim et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, no studies have directly compared CBIT vs. medication. The closest approximation is a study in Italy that compared a package of behavior therapy for tics (combining CBIT and exposure therapy) to antipsychotic medication and to psychoeducation (Rizzo et al, 2018). Results showed that behavior therapy and antipsychotic medication were equally effective in reducing tic severity, and both were superior to psychoeducation.…”
Section: How Does Cbit Compare To Other Treatments For Tics?mentioning
confidence: 99%